Romanian Export Competitiveness on the European Market - Paul Clipa (CES Working Papers, 2011)
Exports of a nation can form a large part of its commercial card on the international market. Global consumer, according to the quality of exports, may associate a certain image about the country of origin. This article aims at explaining the relationship between exports and competitiveness of a nation, the analysis focuses on the nature and intensity of intra-Community exports of Romania. To this end we considered a number of performance indicators that are able to reveal the positioning of trade from Romania to the EU.
Keywords: F14; F15; F16; F40; 330; exports; competitiveness; performance; trade; indicators Romania